Immediate effects of some corrective maintenance interventions on flexible pavements - Qiao, Yaning; Dawson, Andrew; Parry, Tony; Flintsch, Gerardo W. (Taylor and Francis, 2018)
Different maintenance interventions have different ability to address distresses on flexible pavements. Understanding the maintenance effects can benefit pavement maintenance decision-making. In this study, the immediate maintenance effects on roughness and rutting of three interventions including overlay, overlay with an additional base layer and mill and fill were studied and compared. A method was introduced to validate maintenance effect models, using the pavement management information from Virginia Department of Transportation. The method included a data mining process to extract data and apply regression analysis of maintenance effect models. The outliers in the analysis were detected and removed using the method of Cook’s distance. It was found that the immediate maintenance effects of overlay with base layer were greatest and mill and fill was least when treating pavements with moderate roughness (50–100 in/mi (≈ 0.8–1.6 m/km)). However, mill and fill was more useful for treating pavements with high roughness (>100 in/mi (≈1.6 m/km)). Furthermore, suggestions were proposed on data collection for road authorities to improve the prediction of maintenance effects.